Hot Deformation and Microstructure Evolution of Metallic Materials - Schindler, Ivo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Hot deformation is a key method of processing metallic materials and controlling their final properties through structure-forming processes. The ability to exploit the structural potentiality of both traditional alloys and new progressive materials is crucial in terms of sustainable development and economic growth. This reprint focuses not only on conventional technologies (e.g., rolling or forging) but also on modern procedures, such as various types of complex thermomechanical processing and controlled cooling. Most papers are based on the application of advanced hot deformation simulators and structural analysis methods, as well as computer simulations of bulk-forming processes.